Pressure injury prevalence and characteristics in patients with COVID-19 admitted to acute inpatient rehabilitation unit - Weiying Lu; Ona Bloom; Ona Bloom; Melissa Rathgeber; Susan Maltser (Frontiers Media S.A., 2023)
ObjectiveTo investigate the incidence and severity of pressure injuries among COVID-19 patients who required acute hospitalization and subsequent acute inpatient rehabilitation (AIR).DesignData was collected retrospectively from medical charts of COVID-19 patients who were admitted to AIR during April 2020-April 2021.SettingAcute Inpatient Rehabilitation at a single hospital in the greater New York metropolitan area.ParticipantsSubjects included COVID-19 patients (N = 120) who required acute hospitalization and subsequent acute inpatient rehabilitation, of whom 39 (32.5%) had pressure injuries.InterventionsNot applicable.Main outcome measure(s)The incidence, location, and severity of pressure injuries in COVID-19 patients, as well as demographic and clinical characteristics of the acute hospitalization.ResultsAmong patients who developed pressure injuries, more patients received mechanical ventilation (59% vs. 33%, P < 0.05) and tracheostomy (67% vs. 17%, P < 0.00001). The lengths of stay were longer in both the intensive care unit (ICU) (34 vs. 15 days, P < 0.005), and in acute inpatient rehabilitation (22 vs. 17 days P < 0.05).ConclusionPressure injuries were more common in COVID-19 patients who had longer lengths of stay, received mechanical ventilation or tracheostomy, during acute hospitalization. This supports the use of protocols to prioritize pressure offloading in this patient population.